Twentieth-century Chinese translation theory : modes, issues and debates - Chan, Tak-hung Leo, 1954- (Benjamins translation library, 2004)
Past attempts at writing a history of Chinese translation theory have been bedeviled by a chronological approach, which often forces the writer to provide no more than a list of important theories and theorists over the centuries. Or they have stretched out to almost every aspect related to translation in China, so that the historical/political backdrop that had an influence on translation theorizing turns out to be more important than the theories themselves. In the present book, the author hopes to devote exclusive attention to the ideas themselves. The approach adopted centers around eight.